(untitled) (Research, Society and Development, 2021)
Diabulimia or insulin diet is an eating disorder as a practice of omitting or intentionally reducing the dose of insulin, with the aim of losing weight. Objective: To conduct a systemic review on the topic of "diabulimia" in order to understand the general aspects of this eating disorder. Methodology: Five scientific literature platforms were used to search as a database, namely: Scientific Electronic Library Online (SciELO), Lilacs, PubMed, Cochrane Library and Google Scholar. Literature published in Portuguese and English between the years 2018-2021 was used. Results and discussion: From the studies, it was possible to see that diabulimia can cause several complications in the patient in the long term, and may even reduce the life expectancy of studies, involving glucose metabolism. Therefore, it is of fundamental importance that DM1 patients continue to provide continuous and effective multidisciplinary support with endocrinologists, psychologists, physical educators and nurse nutritionists. Conclusion: The main symptomatology related to the complications of diabulimia, through the systematic research of the present work, was weight loss. In addition, among the main factors that make patients with diabetes perform this eating practice, dissatisfaction with the body and decreased self-esteem can be mentioned.